ANALISIS PENGAWASAN DINAS PERHUBUNGAN DALAM UJI LAYAK JALAN ANGKUTAN UMUM KOTA BATAM - Arif, Syamsul Ma; Dompak, Timbul Dompak (LPPM Universitas Putera Batam, 2021)
This research was conducted for understanding how the activities carried out by the Department of Transportation in conducting roadworthiness tests for public transport. By using qualitative descriptive data analysis techniques, in accordance with the results obtained in the field. This study uses 4 indicators of public service management proposed by Robert J Mocler and D.R Gilbert Jr, namely standards, measurement, comparison, action. Problems encountered were related to roadworthy testing of public transport, Standard Operating Procedures that were not socialized, testing equipment that died but had not been repaired, and human resources who did not fully understand transportation testing. In this case, the inhibiting factors of the problems that occur are the socialization process and budget, related to good roadworthiness testing through periodic tests at the Transportation Service Office which is lacking so that public awareness to conduct periodic tests is very low. From the results of the study, it can be concluded that the implementation of the roadworthiness test for public transportation has been going well but is still not fully maximized so it needs to be monitored regularly.